Analisis Tarif Sewa Gedung UPTD Taman Budaya Gerson Poyk Dinas Pendidikan dan Kebudayaan untuk Meningkatkan Pendapatan Asli Daerah Provinsi Nusa Tenggara Timur - Panie, Ketty Natalia; Tameno, Nikson; Molidya, Aldarine (Innovative: Journal Of Social Science Research, 2025)
This research aims to determine the market value of asset and the fair rental of regional asset in the form of the Gerson Poyk Culture Park Building, belonging to the East Nusa Tenggara Provincial Government and its contribution to Regional Original Income. In determining the market value of assets, a cost approach is used, while to determine reasonable rental rates, an approach based on a comparison of market rental data is used. The results of this research show that the estimated market value of assets consisting of the value of land and buildings using the cost approach is IDR 48.936.504.000, while the estimated fair rental rate for assets is IDR 700.000 per day which is the result of a reconciliation of the results of the assessment based on the comparative approach. market rental data. By using reasonable rental rates as a result of this research, the estimated contribution of rentals to Original Regional Income in the regional levies sector is 0.10% and to the building rental revenue target for 2019 to 2023.